"IF THEY'RE ON TIER I, THERE ARE REALLY NO CONCERNS THAT WE CAN SEE:" PBIS MEDICALIZES COMPLIANT BEHAVIOR. - Bornstein, Joshua (Journal of Ethnographic & Qualitative Research)
Inclusive school leaders consider students showing disorderly behavior as their most vexing problem. Seeking to move away from disciplinary responses, they regard Positive Behavioral Interventions and Supports (PBIS) as their most useful systematic tool. The purpose of this research was to understand the discourses that leaders employed in one phase of that work: establishing Tier I universal protocols and expectations. This study conducted a Foucauldian discourse analysis of medicalization and order as expressed by these leaders. The critical discourse analysis unpacked a shift from regarding behavior in a good/bad binary as per discipline codes to a normal/deviant continuum as per the pyramidal structure of PBIS. Rooted in codes of conduct, orderly and compliant behavior fundamentally defined the good student, and in PBIS, the normal student. Practices and protocols such as the ubiquitous and consistent promulgation of behavioral expectations, and the use of Office Discipline Referrals as the primary screening data point highlighted the normalization of compliance. Having been established as normal, compliance was then the baseline condition against which the more diagnostic and therapeutic discourses of upper tiers of PBIS would be measured.